Thermodynamic assessment of a hybrid methane cracking system for liquified hydrogen production and enhanced oil recovery using CO2 - Aliya Banu (17017731) (2022)
Hydrogen fuel production from methane cracking is a cleaner process compared to steam methane reforming due to zero greenhouse gas emissions. Carbon black that is co-produced, is valuable and can be marketed to other industries. As this is a high-temperature process, using solar energy can further improve its sustainability. In this study, an integrated solar methane cracking system is proposed and the efficient utilization of the hydrogen and carbon products is explored. The carbon by-product is used in a direct carbon fuel cell and oxy- combustion. These processes eliminate the need for carbon capture technologies as they produce pure CO2 exhaust streams. The CO2 produced from the systems is used for enhanced oil recovery to produce crude oil. The produced turquoise hydrogen is liquified to make it suitable for exportation. The process is simulated on Aspen Plus®, and its energy and exergy efficiencies are evaluated by carrying out a detailed thermodynamic analysis. A reservoir simulation is used to study the amount of oil that can be produced using the captured CO2. The overall system is studied for oil production over 20 years and energy and exergy of efficiencies 42.18% and 40.18%, respectively were found. Enhanced oil recovery improves the recovery rate from 24.8% to 64.3%. Other Information Published in: Energy Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.egyr.2022.10.124